Hubungan antara bimbingan belajar orang tua dan penerapan kurikulum 2013 dengan sikap siswa kelas iv sekolah dasar - Halimah Halimah; Jenny Indrastoeti Siti Poerwanti; Siti Istiyati (Didaktika Dwija Indria, 2021)
The purpose of this research is to find out the relationship between parent’s guidance and the application of curriculum 2013 toward student’s attitude of 4th grade primary school students. The form of this research was  quantitative correlation. The sample of this research were the students of fourth grade of elementary school in Ngemplak, sub-district of Boyolali regency academic year 2018/2019.  Data collection techniques are conducted by questioner, observation, and document analysis. Data analysis technique is a quantitative inferensial technique. The conclusion  of this research is ‘there is a positive relationship between parent’s guidance and the application of curriculum 2013 toward student’s attitude of 4th grade primary school students’